2021
DOI: 10.3389/fnins.2021.615363
|View full text |Cite
|
Sign up to set email alerts
|

Personal Resources and Organizational Outcomes: Sex as a Moderator of the Complex Relationships Between Self-Esteem, Heart Rate Variability, and Work-Related Exhaustion

Abstract: Global self-esteem represents a protective personal resource lowering the risk of psychological distress. Research conducted in the work setting has confirmed the psychosocial benefits of high self-esteem. However, research linking self-esteem to neurobiological adaptability appears quite scarce. In this study, we propose a theoretical model in which self-esteem predicts work-related exhaustion indirectly, through the mediation of heart rate variability (HRV) and negative affect at work. Moreover, we explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
(94 reference statements)
2
8
0
Order By: Relevance
“…Prevention interventions engage with expectations, role definition, sharing of feelings, and ambition [117]. Burnout prevention takes into account the different realities of groups [118]; the need for increased training, mentorship, peer support, supervision, organizational culture, and interdisciplinary licensure efforts [18]; the interaction between personal and situational factors [15]; sex differences in how individuals respond to work-related stress [119]; and the need to increase a sense of belonging [120]. Burnout preventions deal with the root causes of burnout [121]; individual vulnerability and situational stressors [122]; self-initiated efforts focusing on resources and demands in the workplace, home, and personal domain [123]; and improvement of organizational culture [111].…”
Section: Burnout and The Workplacementioning
confidence: 99%
“…Prevention interventions engage with expectations, role definition, sharing of feelings, and ambition [117]. Burnout prevention takes into account the different realities of groups [118]; the need for increased training, mentorship, peer support, supervision, organizational culture, and interdisciplinary licensure efforts [18]; the interaction between personal and situational factors [15]; sex differences in how individuals respond to work-related stress [119]; and the need to increase a sense of belonging [120]. Burnout preventions deal with the root causes of burnout [121]; individual vulnerability and situational stressors [122]; self-initiated efforts focusing on resources and demands in the workplace, home, and personal domain [123]; and improvement of organizational culture [111].…”
Section: Burnout and The Workplacementioning
confidence: 99%
“…Second, we explored the potential moderating role of biological sex in the relationship between perceptions of supervisor and coworkers’ support and daily HRV. This prediction was based on the above-reviewed studies suggesting sex differences in (a) the use of social confrontation strategies, with women utilizing more to tend-and-befriend responses to cope with stressors and men utilizing more to fight-or-flight responses (Taylor, 2011); (b) sex differences in physiological processes associated with self-regulation (Koenig & Thayer, 2016), with more parasympathetic modulation of the heart for women compared with men; and (c) previous empirical findings of sex differences in the relationship between self-esteem, often considered as a gauge of social inclusion status (De Longis et al, 2021; Perinelli et al, 2022). Finally, we controlled the association between social support at work and HRV for potential confounders such as age, negative work events, caffeine, nicotine, and BMI which have been found to be significantly correlated with HRV in previous similar studies (De Longis et al, 2020).…”
Section: The Present Studymentioning
confidence: 99%
“…For example, Lischke and colleagues (47) found that resting HRV was associated with an increase in self-reported functional (but not dysfunctional) emotion regulation strategies (i.e., reappraisal) for men but not for women (47). De Longis and colleagues (48) found that self-esteem was negatively related to HRV for women but was not significantly related for men. The authors (47,48) interpreted these sex-specific associations as reflecting interindividual differences in prefrontal-paralimbic engagement during emotion regulation.…”
Section: A Moderating Role Of Sex?mentioning
confidence: 99%
“…De Longis and colleagues (48) found that self-esteem was negatively related to HRV for women but was not significantly related for men. The authors (47,48) interpreted these sex-specific associations as reflecting interindividual differences in prefrontal-paralimbic engagement during emotion regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation